(Re)Defining Queer and Trans* Student Retention and "Success" at Historically Black Colleges and Universities. (February 2020) - Mobley, Steve D.; Hall, Leslie
Unfortunately, within the extant scholarship that has explored queer and trans* historically Black college and university (HBCU) students, the discourse(s) that deliberately center how they can be retained, persist, and ultimately graduate have largely been absent from the literature. Thus, this conceptual exploration offers strategies that HBCUs can and should utilize to ensure that their queer and trans* students persist and graduate. A practice-oriented model is also presented to serve as a guide for HBCU student affairs practioners, presidents, and faculty members to implement so that they may inculcate environments of "success" for their queer and trans* students. Ultimately, the "Queer and Trans* HBCU Student Engagement and Retention Practice Model" illustrates how HBCUs can engage their queer and trans* students during admissions or recruitment, matriculation, and even as alumni.